Detection of formalin in fish and milk and perception of the household-heads on formalin contamination in Bangladesh (Bangladesh Journal of Nutrition, 2018)
Bangladeshi people are consuming fish and milk almost every day. Bangladesh imports selected type of carp fish from neighboring countries. Mixing of formalin in fish and milk as preservative is known to many people. The study aimed to determine the presence of formalin in fish and milk at the household level throughout the country. Multistage sampling was done to select 210 households of 7 divisions of Bangladesh. Qualitative information was collected from fish retailers and consumers about the use of formalin in fish and milk. Detection of formalin was carried out on fish samples from 6 wet markets in Dhaka city and 210 selected households. Pasteurized liquid milk from Dhaka city markets and cow milk from selected 210 households were tested using formalin detection kit developed by BCSIR. The Focus Group Discussion (FGD) respondents stated that they do not add chemicals or formalin in fish. But 70% of the respondents ensured that imported fishes and small fishes namely Kaachki fish collected from Mymensingh and Chittagong are contaminated with formalin. Majority of them said that dishonest businessmen usually add formalin during off-loading of fish from the vehicle or at wholesale level or at cold storage. Formalin was found in 46 out of 70fish samples in Dhaka city. But 384 fish samples and 210 cow milk samples from 210 households and 12 milk samples of 3 popular brands in Dhaka city were found free from formalin. Local fishes were formalin free because the fisherman catches fish locally and sale those in local market within 3 to 4 hours even without using ice for preservation. Most of the household heads were educated and from middle income group who had good perception about formalin contamination. The study also indicated that 92% of household heads agreed to spend 5 to 10% extra cost for formalin free food. It reveals that formalin use is not a severe problem so far in rural markets but exists as a threat in the city markets.Bangladesh J. Nutr. Vol. 28-31, December 2018, P: 65-72